2006
DOI: 10.1055/s-2005-870412
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Endorectal Ultrasound Using a New Freehand Software Program: Results in 35 Patients with Rectal Cancer

Abstract: Three-dimensional ERUS is easy to carry out using this new software program. There is no need for an external sensor mounted at the tip of the probe, and manipulation of the rectal probe is facilitated. Three-dimensional ERUS can be carried out using linear and radial electronic probes with the same ultrasound equipment. Three-dimensional ERUS allows more precise staging of lesions and better definition of the mesorectal margins, and this has a direct impact on therapeutic decision-making in patients with rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 13 publications
(17 reference statements)
4
21
0
2
Order By: Relevance
“…Curved linear array echoendoscopes use an electronic transducer and they offer the ability to perform interventional procedures such as FNA under real-time visualization [6]. New techniques that have contributed significantly to the evolution of ERUS include three-dimensional ERUS [7], high-frequency miniprobes, transrectal ultrasound-guided biopsy techniques, and hydrogen peroxide-enhanced endosonography [8]. ERUS-FNA is usually well tolerated under conscious sedation on an outpatient basis similar to other endoscopic procedures [6].…”
Section: Discussionmentioning
confidence: 99%
“…Curved linear array echoendoscopes use an electronic transducer and they offer the ability to perform interventional procedures such as FNA under real-time visualization [6]. New techniques that have contributed significantly to the evolution of ERUS include three-dimensional ERUS [7], high-frequency miniprobes, transrectal ultrasound-guided biopsy techniques, and hydrogen peroxide-enhanced endosonography [8]. ERUS-FNA is usually well tolerated under conscious sedation on an outpatient basis similar to other endoscopic procedures [6].…”
Section: Discussionmentioning
confidence: 99%
“…Both of these advantages had a direct impact on therapeutic decision making for patients with rectal cancer [22].…”
Section: Cancermentioning
confidence: 99%
“…[48][49][50][51] Assessment of additional scan planes and volume reconstructions facilitate the understanding of three-dimensional anatomy and improve the evaluation of the depth of tumor invasion. 17 Giovannini et al 50 reported that the mesorectal margins are defined better using threedimensional ERUS than two-dimensional ERUS. In 6 of 15 patients classified as having T3N0 lesions, three-dimensional ERUS revealed malignant lymph nodes, a finding that was confirmed surgically in five of the six cases.…”
Section: Rectal Tumorsmentioning
confidence: 99%